SCIENTIFIC RESEARCH IN THE FIELD OF CHOREOGRAPHY ART IN UZBEKISTAN - Usmanova Gulasal Normukhammad qizi; Komarova Olga Konstantinovna; Ataxanov Shavkat Djurabayevich; Abdiyeva Gulishod Esonbekovna; Sultanova Lola Aleksandrovna (Utilitas Mathematica, 2025)
The scientific approach, scientific study, encompasses historical, theoretical, and critical criteria in every discipline. Creative products of the performing, "live" arts - plays, dances, live concerts - are performed before the eyes of the audience and pass in an instant. They can be recorded on video. However, the perspectives of theater and pop directors, choreographers, aimed at live dialogue (artist-spectator) are not taken into account, and live works of art lose their specific charm. In this sense, world art and dance studies have studied and promoted the artistic styles of ballet masters throughout their long history. Art historians, who are considered advanced viewers, have deeply felt and conveyed to the audience the aesthetic, educational, attractive, and lively aspects of the artistic and integral dance masterpieces. In Uzbekistan, in 1928, on the initiative of M. Koriyakubov, the Institute of Choreography and Music was established, later renamed the “Scientific Research Institute of Art Studies”. At that time, the Institute of Art Studies began scientific research on the heritage of Uzbek dance in Samarkand, and then in Tashkent. In Leningrad, ethnographer I.G. Bakhta, together with the famous Uzbek musicologist E.E. Romanovskaya, recorded the dance series “Katta yimen” from the Fergana dance school. “Katta yimen” was also recorded, interpreted in the styles of the great masters of Uzbek choreography, Master Olim Kamilov and Yusuf Uzbek Shakarjanov.